From multiculturalism to interculturality: through the relational reason (Memorandum: Memória e História em Psicologia, 2013)
Multiculturalism is a term which was spread in the West during the 1960s to indicate respect, tolerance and defence of cultural minorities. The idea of multiculturalism has become a collective imaginary ("all different, all equals"). It has generated a political ideology supporting an inclusive citizenship towards "different" cultures. After being adopted as official policy in many Countries, multiculturalism has generated more negative than positive effects (fragmenting the society, separating the minorities and creating public cultural relativism). As a political doctrine, it seems harder and harder to be put into practice. At its place, today we talk of interculturality. But this expression also seems quite vague and uncertain. This essay discusses the possible alternatives to multiculturalism, asking itself whether the way of interculturality can be a solution or not. The Author's thesis is that the theory of interculturality has the advantage to stress the inter, namely what lies in between different cultures. But it does not possess yet the conceptual and effective means to understand and handle the problems of the public sphere, when the different cultures express radical cultural values that bring about conflict between them. The troubles of interculturality result from the lack of two things: an insufficient reflexitivity inside the single cultures, and the lack of a relational interface between the different cultures (between the carrier subjects). Modern western Reason created a societal structure (lib-lab) promoting neither the first nor the second one. In fact, it neutralizes them, because it faces the dilemmas of values inside the cultural diversities through criteria of ethical indifference. Such criteria set reflexitivity to zero, preventing individuals from understanding the deepest reasons of the vital experience of the others. Reason is emptied of its meaning and of its understanding capability. To go over the failures of multiculturalism and the frailties of interculturality, a lay approach to the coexistence of cultures is required, being able to give strength back to Reason, through new semantics of the inter-human diversity. The Author suggests the development of the "relational reason", beyond the forms already known of rationality. To make Reason relational might be the best way to imagine a new social order of society, being able to humanize the globalizing processes and the growing migrations. The after-modern society will be more or less human depending on how it will be able to widen the human Reason, structuring it inside a new "relational unit" with the religious faith.